Visible and near IR photoluminescent response of nc-Si: er thin films produced by rf sputtering - Cerqueira, M. F. (2004)
In this contribution we present the Visible and near IR photoluminescence (PL) analysis of Er doped nanocrystalline silicon thin films produced by rf magnetron sputtering method. Efficient photoluminescence was observed in these structures in both visible and 1.54µm wavelength regions. We show the strong influence of the presence of nanocrystalline fraction in films on their luminescence efficiency at 1.54 μm that has been studied on the series of specially prepared samples with the different crystallinity, i.e. percentage and sizes of Si nanocrystals. The mechanism involved in the visible photoluminescence of highly a crystalline nc-Si:H consisting of about 7 nm silicon nanocrystals embedded in an amorphous matrix is discussed.